Real exercise for real people finding your optimum level of physical activity for a lifetime of healthy living - Francis, Peter R (Prima Publishing, 1996)
This book offers diagnostic tests to determine flexibility, strength, and the likelihood of injury for your body type. The authors provide guidelines for developing effective exercise programs that can be incorporated into any lifestyle.